2014
DOI: 10.1098/rsif.2013.1057
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and characterizing a bioactive small molecule and microRNA association network for Alzheimer's disease

Abstract: Alzheimer's disease (AD) is an incurable neurodegenerative disorder. Much effort has been devoted to developing effective therapeutic agents. Recently, targeting microRNAs (miRNAs) with small molecules has become a novel therapy for human diseases. In this study, we present a systematic computational approach to construct a bioactive Small molecule and miRNA association Network in AD (SmiRN-AD), which is based on the gene expression signatures of bioactive small molecule perturbation and AD-related miRNA regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…First, we computed the Meet/Min score for each pair of miRNAs to evaluate the extent of shared target genes [15, 16]. The Meet/min score between two miRNAs was defined as the number of common target genes of two miRNAs divided by the small number of target genes of the two miRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we computed the Meet/Min score for each pair of miRNAs to evaluate the extent of shared target genes [15, 16]. The Meet/min score between two miRNAs was defined as the number of common target genes of two miRNAs divided by the small number of target genes of the two miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the structure based method, Jiang et al proposed a novel method to construct small molecule-miRNA networks for 23 different cancers based on the similarity of transcriptional responses [15]. Similar work has also been done for Alzheimer's disease [16]. However, since lack of miRNA-transfected datasets, we simulated the transcriptional responses of miRNA perturbation through intersecting target genes and differential expressed genes of specific disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are many strategies that can be used to inhibit or overexpress miRNA of interest. Several of these strategies are in pipeline for neurodegenerative diseases (Meng et al, 2013) but it will be interesting to see if these methods/strategies are useful in the complex disorders such as MDD.…”
Section: Can Mirnas Severe As Therapeutic Targets and In The Developmmentioning
confidence: 99%
“…Further analysis of the positive connections (quinostatin and miR-148b, amantadine and miR-15a) and the negative connections (melatonin and miR-30e-5p) indicated that our large-scale predictions afforded specific biological insights into AD pathogenesis and therapy. This study proposes a holistic strategy for deciphering the associations between small molecules and miRNAs in AD, which may be helpful for developing a novel effective miRNA-associated therapeutic strategy for AD (Meng et al, 2014). Augmenting BDNF/TrkB signaling has been demonstrated to be a promising strategy for reversing cognitive deficits in preclinical models of Alzheimer disease (AD).…”
Section: Other Ad Treatment Productsmentioning
confidence: 99%